Evaporation of Adherent Al-Films on Single Crystalline LiNbO3 Substrates - E. Schippel (Active and Passive Electronic Components)
LiNbO3 is used as a single crystalline substrate material for the manufacturing of surface acoustic wave devices as frequency selective components. On the polished substrate wafer, Al with a film thickness of about 400 nm is evaporated in a high vacuum.